Pemuda dan Wirausaha Maskertie Dye Aposteriorinya Berinovasi serta Kreativitas di Masa Pandemi - Anis Febriana Sita Hidayati (LP2M IAIN Sultan Amai Gorontalo, 2023)
Abstract: Masks are widely recognized as essential tools for safeguarding individuals from various pollutants, particularly air contaminants. Moreover, in the current prevailing situation marked by the prevalence of Covid-19, masks play a pivotal role in mitigating the risk of viral transmission. Among the varieties of masks available, tie-dye masks have emerged as innovative solutions characterized by their appealing color range. The primary material used in crafting tie-dye masks is fabric, a sustainable alternative to disposable medical masks that pose environmental disposal challenges. This study explores the transformative role of young entrepreneurs as change agents, focusing on their entrepreneurship endeavors related to tie-dye cloth masks. The objective is to gain insights into the activities undertaken by the younger generation in response to the challenges posed by the pandemic. The research was conducted in multiple locations, including Cepu, Blora Regency, Central Java, Ngadirejo, Kartasura, Central Java, and Kartasura Village, Sukoharjo, Central Java. The research subjects encompass young entrepreneurs within these areas. Data collection involved a combination of observation, using mobile devices for recording, and interviews with various sources. The findings underscore the growing importance of tie-dye masks, particularly during the pandemic. Their reusability, attainable through simple washing, makes them a practical choice. Despite the pandemic's constraints, the younger generation has harnessed this demand for tie-dye masks as a means to explore new business opportunities and nurture their creative abilities. The active involvement of the younger generation stands as a significant force driving entrepreneurship, particularly amid the ongoing pandemic crisis. Keywords: Mask; Pandemic; Tie Dye; The Role of The Younger Generation.